The electron-phonon interaction in GaAs/(AlGa)As quantum wells - Cross, Andrew John (2001)
This thesis presents a study of the electron-phonon interaction in two dimensional electron gases (2DEGs), by measuring of the acoustic phonon emission from a sequence of n-type doped GaAs/(AlGa)As quantum wells. Previous studies of emISSIon from 2DEGs confined in GaAs heterojunctions (Chin et al., 1984) have shown a surprising absence of longitudinal acoustic (LA) mode phonon emission, in contrast with theoretical studies (Vass, 1987) which predict that deformation potential coupled LA mode emission should dominate the energy relaxation processes. This may be attributed to the finite width of the quasi-2D sheet, which imposes a restriction on the maximum emitted phonon wavevector component perpendicular to the 2DEG, leading to a suppression of the emission (the "1Iao cutoff') at smaller phonon wavevectors than predicted by the earlier theory. By using the quantum well width w as a means of modulating the thickness of the 2DEG, the dependence of the 1Iao cutoff on the phonon emission can be directly measured. In the present work, significant LA phonon emission from the quantum well samples is observed. To complement the experimental measurements, the theory of emission from a 2DEG has been modelled in detail using computer simulation techniques. Calculations of the electron-phonon interaction, including matrix element anisotropy and dynamic screening, as well as phonon focusing effects, can be combined to produce accurate predictions of the experimentally detected phonon emission energy spectra.